Mismatch Negativity to Threatening Voices Associated with Positive Symptoms in Schizophrenia - Chen, Chenyi; Liu, Chia-Chien; Weng, Pei-Yuan; Cheng, Yawei (Frontiers in Human Neuroscience, 2016)
Although the general consensus holds that emotional perception is impaired in patients with schizophrenia, the extent to which neural processing of emotional voices is altered in schizophrenia remains to be determined. This study enrolled 30 patients with chronic schizophrenia and 30 controls and measured their mismatch negativity (MMN), a component of auditory event-related potentials (ERP). In a passive oddball paradigm, happily or angrily spoken deviant syllables dada were randomly presented within a train of emotionally neutral standard syllables. Results showed that MMN in response to angry syllables and angry-derived nonvocal sounds was significantly decreased in individuals with schizophrenia. P3a to angry syllables showed stronger amplitudes but longer latencies. Weaker MMN amplitudes were associated with more positive symptoms of schizophrenia. Receiver operator characteristic analysis revealed that angry MMN, angry-derived MMN, and angry P3a could help predict whether someone had received a clinical diagnosis of schizophrenia. The findings suggested general impairments of voice perception and acoustic discrimination in patients with chronic schizophrenia. The emotional salience processing of voices showed an atypical fashion at the preattentive level, being associated with positive symptoms in schizophrenia.